Communicating science in international English: scholarly journals, publication praxis, language domain loss and benefits - Cianflone, Eugenio (Círculo de Lingüística Aplicada a la Comunicación, 2014)
The leading role of English as the international language of scientific communication has been extensively studied. Available data show that English exerts powerful effects in publication praxis since the use of a common idiom, or Lingua Franca, serves two main assets: to gain international visibility, funding and career advancement and to cater for the worldwide communication of ideas among subjects with different linguistic backgrounds. Aim of this paper is to discuss contemporary publication praxis following specific datasets: the growth of scholarly journals, the publication output in English compared to other national languages, how this situation affects communication in writing and in reading for scholarly research.